The role of the connection between intestinal microbiota and brain in the pathogenesis of functional gastrointestinal disorders - Nikolovska-Trpčevska, Emilija (Centre for Evaluation in Education and Science (CEON/CEES), 2023)
The relation between the intestinal microbiota and the brain is an important field of research in the pathophysiology of functional gastrointestinal disorders (FGIDs). This group of diseases includes more than 40% of the population and is one of the most common reasons for the need of consulting a gastroenterologist. The interaction between the gut microbiota and the brain is a new terminology for defining functional gastrointestinal disorders, based on certain diagnostic criteria. The ROMA IV classification of diagnostic criteria divides functional gastrointestinal diseases into five anatomical regions including the esophagus, gastroduodenal tract, intestine, biliary tract, and anorectal region. Symptoms are usually based on gastrointestinal dysfunction such as gastroesophageal reflux disease (GERD), functional dysphagia, functional dyspepsia, gastroparesis, irritable bowel syndrome (IBS), functional constipation, diarrhea, and fecal incontinence. In this study, we observe at the mechanisms of interaction between gut microbes and brain function. Enteric microbiota (nonpathological microorganisms) has numerous synergistic actions with the human body. The microbiota can change and is different in each individual, as each individual has their own specific microbiome. From digesting food to protecting against pathogens, the intestinal microbiota plays an important role in maintaining immunity and homeostasis. Recently, studies have shown that one of the main impeler of the interaction between the gut and the brain is precisely the microbiome, and so the new term was created "axis of intestinal microbiota-brain". In the future, the general approach to the treatment of functional gastrointestinal disorders tends to be personalized, not only based on symptoms, but also on the underlying pathophysiology and psychology. Various mechanisms, including metabolic pathways, immune system, neural pathways, are involved in the relationship between the gut microbiota axis and the brain. We also discuss some future challenges in modifying the intestinal microbiota with probiotics, prebiotics and nutrition, precisely through this new relationship. Awareness of the relationship between intestinal bacteria and their hosts is crucial in the development of modern therapeutic strategies based on good microorganisms (pre/probiotics) for functional gastrointestinal disorders.